2005
DOI: 10.1149/1.1943587
|View full text |Cite
|
Sign up to set email alerts
|

LSGM-Based Solid Oxide Fuel Cell with 1.4 W/cm2 Power Density and 30 Day Long-Term Stability

Abstract: A single solid oxide fuel cell (SOFC) with a normalLa0.8normalSr0.2normalGa0.83normalMg0.17normalO2.815 (LSGM) electrolyte 200μm thick with H2 as fuel gave 1.4W∕cm2 peak power density at 800°C . With a normalLa0.4normalCe0.6normalO1.8 (LDC) buffer layer 20μm thick between the electrolyte and the two electrodes, a 30-day test showed essentially no degradation of the output power. The tests demonstrated the feasibility of an SOFC operating at temperatures T<800°C with LSGM as the electrolyte. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 16 publications
(19 reference statements)
2
36
0
Order By: Relevance
“…Sr-and Mg-doped lanthanum gallate (LSGM) is considered to be a promising alternative electrolyte material because of its higher oxide ionic conductivity and oxygen transport number [4,5]. In recent years, there have been many studies on the performance of SOFCs using a thick LSGM electrolyte support [6,7]. However, the ohmic resistance of the thick electrolyte was still larger than that of the electrodes, although the electrode polarization loss became dominant at 700°C [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sr-and Mg-doped lanthanum gallate (LSGM) is considered to be a promising alternative electrolyte material because of its higher oxide ionic conductivity and oxygen transport number [4,5]. In recent years, there have been many studies on the performance of SOFCs using a thick LSGM electrolyte support [6,7]. However, the ohmic resistance of the thick electrolyte was still larger than that of the electrodes, although the electrode polarization loss became dominant at 700°C [7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been many studies on the performance of SOFCs using a thick LSGM electrolyte support [6,7]. However, the ohmic resistance of the thick electrolyte was still larger than that of the electrodes, although the electrode polarization loss became dominant at 700°C [7]. Thus, it is expected that further improvement in cell performance can be achieved by an anode-supported SOFC using a thin LSGM electrolyte film, owing to the reduced electrolyte resistance loss.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the presence of minor electronic conductivity in the electrolyte can improve the electrode kinetics, as has been reported for ceriabased materials [9,10], enhancing the electrode/electrolyte interface polarisation. [11,12] and SrCo 0.8 Fe 0.2 O 3-d (SCF) [13][14][15] due to their high oxygen fluxes and favourable oxygen-reduction performance at intermediate temperatures [16][17][18][19]. Nevertheless, Co is too expensive and Co-based compounds usually display too high thermal expansion coefficients compared to other cell components [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Ralph et al [3] have studied potential cathode materials using yttria-stabilised zirconia (YSZ) and gadolinia doped ceria (CGO) electrolytes for intermediate and low temperature applications, respectively. These authors found that ferrites and cobaltites showed the best performances in YSZ However, Ni-free anodes such as La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3−δ (LSCrM) [14,15] have been successfully tested using doped lanthanum gallates as electrolytes [16][17][18]. The work recently reported by Huang et al [19] confirms the viability of LSCrM under fuels with low sulphur contents, although they have suggested a new composition based on a double perovskite, i.e.…”
Section: Introductionmentioning
confidence: 99%